PENGARUH HUBUNGAN INTERPERSONAL DAN EFEKTIVITAS KERJA TERHADAP KUALITAS PELAYANAN PUBLIK: Studi Empiris Pada Kantor Basarnas Medan - Nashrudin Setiawan; Hasrul Azwar Hasibuan; Abdi Setiawan (Universitas Methodist Indonesia, 2018)
This research aims to analyze the effect of interpersonal relationships and work effectively on public service quality in the National SAR Agency (BASARNAS). This research is a quantitative research using 53 respondents as the samples. A multiple regression analysis was used to analyze the data. The research findings indicate that interpersonal relationships and work effectiveness have a positive and significant effect on public service quality.